Reimagining peace, reimagining education: Peace educational potential of social media - M. Ayaz Naseem (TARBIYA: Journal of Education in Muslim Society, 2015)
Abstract In this paper I examine the potential of blogosphere for civic education. My main argument is that in in-crisis societies such as Pakistan the blogosphere is a space where conversations and multilogues on issues that are crucial to societal regeneration are taking place. These conversations and multilogues in/through the blogosphere are democratic and inclusive in that they are not confined by the traditional articulations of ‘expertise’, privilege and subject positioning. Neither the writer nor those who participate in the ensuing conversation are or have to be experts in a disciplinary sense. They are not privileged by credentials or by their positioning in the ‘knowledge’ hierarchy. Any and all agents of the civil society can either start or engage in these multilogues, many of which directly or indirectly, focus on issues of national and societal self-regeneration. Abstrak Dalam makalah ini saya meneliti potensi ruang-blog (blogosphere) untuk pendidikan kewarganegaraan. Argumen utama saya adalah bahwa dalam masyarakat yang sedang dilanda krisis seperti Pakistan ruang-blog (blogosphere) merupakan ruang di mana percakapan dan interaksi percakapan tentang isu-isu yang sangat penting bagi regenerasi sosial, berlangsung. Percakapan dan multilogues melalui ruang-blog ini bersifat demokratis dan inklusif karena tidak dibatasi oleh artikulasi tradisional yang mencirikan 'keahlian', pengaturan posisi berdasarkan hak istimewa dan subjek masalah. Baik penulis maupun orang-orang yang berpartisipasi dalam percakapan tidak harus ahli dalam disiplin tertentu. Mereka tidak diberi hak istimewa atas dasar prestasi atau posisi mereka dalam hirarki 'pengetahuan' . Setiap dan semua masyarakat sipil dapat memulai atau terlibat dalam interaksi percakapan ini, banyak di antara mereka yang baik langsung maupun tidak langsung, berfokus pada isu-isu regenerasi diri di tingkat nasional dan masyarakat.How to Cite : Naseem, M., A. (2015). Reimagining Peace, Reimagining Education: Peace Educational Potential of Social Media. TARBIYA: Journal Of Education In Muslim Society, 2(1), 1-11. doi:10.15408/tjems.v2i1.1474. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v2i1.1474